TOKO ONLINE “WARUNG DESA” UNTUK PETANI DI DESA CINOYONG KECAMATAN CARITA KABUPATEN PANDEGLANG-BANTEN - Kusumawati, Berlianingsih; Masduki, Uki; Maryama, Siti; Artha, Tatum; Syamsu, Muhajir (Jurnal Abditani, 2024)
This goal is to facilitate the marketing media of agricultural products. Partners and locations of activities carried out on farmers in Cinoyong Village, Carita District, Pandeglang-Banten Regency. The implementation technique is carried out through the practice of making online stores, socializing and training on the operation of online stores. The approach methods used include the Community development Model, Participatory Rural Appraisal (PRA) Model, Educational, and Persuasive. The result of this community activity is the creation of an e-commerce or online shop www.warungdesaku.com which has been published and can be accessed by the wider community. The online shop that has been built is then socialized and held training for partners. So that partners understand how e-commerce works. the marketing mechanism through the online shop www.warungdesaku.com still uses a special administrator. Administrator is a bridge for farmers and buyers. Some of the products that have been marketed through www.warungdesaku.com are various taro chips, cassava chips, noni fruit, melinjo chips. It is hoped that this online store will provide benefits for farmers.